2022
DOI: 10.3390/cancers14174251
|View full text |Cite
|
Sign up to set email alerts
|

CC Chemokine Ligand-2: A Promising Target for Overcoming Anticancer Drug Resistance

Abstract: CC chemokine ligand-2 (CCL2), a proinflammatory chemokine that mediates chemotaxis of multiple immune cells, plays a crucial role in the tumor microenvironment (TME) and promotes tumorigenesis and development. Recently, accumulating evidence has indicated that CCL2 contributes to the development of drug resistance to a broad spectrum of anticancer agents, including chemotherapy, hormone therapy, targeted therapy, and immunotherapy. It has been reported that CCL2 can reduce tumor sensitivity to drugs by inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 98 publications
0
10
1
Order By: Relevance
“…Our study found a distinct mechanism that GAF was an extraneous factor promoting continuous ERK1/2 activation in GBM cells. Moreover, CCL2 secreted by GAFs induced chemoresistance of GBM cells through MEK1/2-ERK1/2 signaling activation, rather than previously reported CCL2-mediated PI3K/AKT activation 26 . We also successfully validated our findings of the relationship between GAFs and chemoresistance of GBMs by ex vivo GBO models, which encouraged us to take advantage of the patient-derived organoids to assess the chemoresistance-promoting role of GAFs in GBMs and conduct preclinical investigations to target GAF-GBM interplay.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Our study found a distinct mechanism that GAF was an extraneous factor promoting continuous ERK1/2 activation in GBM cells. Moreover, CCL2 secreted by GAFs induced chemoresistance of GBM cells through MEK1/2-ERK1/2 signaling activation, rather than previously reported CCL2-mediated PI3K/AKT activation 26 . We also successfully validated our findings of the relationship between GAFs and chemoresistance of GBMs by ex vivo GBO models, which encouraged us to take advantage of the patient-derived organoids to assess the chemoresistance-promoting role of GAFs in GBMs and conduct preclinical investigations to target GAF-GBM interplay.…”
Section: Discussioncontrasting
confidence: 77%
“…Among cytokine-encoding genes cataloged in the Cytokine Registry (https://www.immport.org/resources/cytokineRegistry), CCL2 expressed at a significantly higher level in the GAFs compared to GBM cells (Figure 4A). Recently, accumulating evidence suggested that CCL2 not only mediated chemotaxis of several immune cells but also could induce multiple solid tumors resistant to a broad spectrum of anticancer drugs [26][27][28] . Correlation analysis showed that GAF was positively associated with the expression level of CCL2 in both IDH-wildtype and IDH-mutant gliomas (Figures 4B and S4A).…”
Section: Gafs Promote Tmz Resistance Of Gbm Cells By Preferentially S...mentioning
confidence: 99%
“…10A–D ). Previous studies have demonstrated that CCL2 can recruit MDSCs infiltration to form an immunosuppressive microenvironment, which helps tumor cells evade the attack of immune cells and supports tumor cell proliferation [ 26 ]. Since CCL2, as a secreted factor, plays a role in immune cell chemotaxis through the CCR2 receptor, we extracted the supernatants of cultured tumor cells for ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, CCL2 was newly detected in the on-chip co-culture with vessels. CCL2 is known to support tumor development, migration and concurrently resists anti-cancer drugs by reducing sensitivity to drug and apoptosis [69][70][71]. More detailed results can be derived using the platform, yet, the importance of endothelium in drug resistance evaluation should be reconsidered.…”
Section: Direct Harvest Of On-chip Tumor Samples and Secretome/gene E...mentioning
confidence: 99%